Rural Entrepreneurship through Cow Based Products - K.S. Tyagi; D.P. Singh; T.C. Sharma; R.K. Gupta (Dr. Chinmay Pandya, 2018)
Indian agriculture is typically characterized by an essential symbiosis of crop and livestock production. Cattle rearing contribute substantially to economic and nutritional security of rural households.  Lately, there has been a concern about viability of cattle husbandry at domestic household level mainly because of low milk yield and increased cost of maintaining cattle without substantial land under farming.  The  Department of Rural Studies and Sustainability at Dev  Sanskriti Vishwavidyalaya (DSVV), Haridwar has developed eleven technologies for cow urine and cow dung  based products viz. soaps, face pack, tooth powder, dhup batti, eye drops, distilled cow urine (Ark), pain-relief massage oil etc. These value added products has helped over 52 cattle owners to make cattle husbandry a profitable enterprise. Besides promotion of cow based therapies, it has provided substantial opportunities for employment of unskilled and semi-skilled youths in rural areas.  Over 50 large cow urine and dung based products production units are presently operating in various parts of the country based on the training imparted at DSVV. The paper describes value added products which can be manufactured using cow dung and urine and can help in enhancing income of cattle owners.